Production efficiency of two demersal finfishes in the trawling grounds off Veraval - Vivekanandan, E (Indian Journal of Fisheries, 2011)
The feeding rate of Nemipterus japonicus in the trawling grounds off Veravaldecreased with advancing age from 5.8% body weight/day (age: 0.1-0.5 year) to4.0% bw/d (3.0-3.5 y) with an average of 4.7% bw/d. The production efficiency was0.06. i.e. 6% of the consumed food was converted for growth. The feeding rate ofSaurida tumbil also decreased with advancing age from 10.8% bw/d (age: 0.2-0.5y) to 7.8% bw/d (4.0-4.5 y) with an average of 9.1% bw/d. The production efficiencywas 0.03. The annual food consumption of the exploited biomass (27131) ofboth the species was 60.923 t. The annual food consumption of the two specieswas almost equal to that of the total trawl landings at Veraval. indicating highpredation mortality in the ecosystem.